Nanotechnology for tissue engineering - Webster, Thomas J. (Henry Stewart Talks, 2007)
Nanomedicine, Nanotechnology, Tissue engineering, Orthopaedics, Cartilage, Vascular, Bladder, Central and peripheral nervous system